Effect of training day, match, and length of the microcycle on workload periodization in professional soccer players: a full-season study - M. Oliva-Lozano, José; Gómez-Carmona, Carlos D.; Fortes, Víctor; Pino-Ortega, José (Biology of Sport, 2022)
The aims of this study were to: (a) describe and compare the volume and intensity from the workload of professional soccer players between training and MD, and (b) analyse the effect that the length of the microcycle had on the workload. A cohort study was designed for a full season in La Liga 123. Wearable tracking systems collected the distance covered in meters (m), total number of high-intensity accelerations (ACCHIGH) and decelerations (DECHIGH), total number of high-speed running actions (HSRA), high-speed running distance (HSRD), high metabolic load distance (HMLD), and player load (PL) from training days (MD+1, MD-4, MD-3, MD-2, and MD-1) and MD. Significant differences were found between training and MD workload, MD workload being the most demanding for all intensity and volume variables (F = 36.35–753.94; p < 0.01; wp 2 = 0.21–0.85). The greatest training intensity and volume were found on MD-4 and MD-3 (p < 0.05). In addition, a novel finding was that the length of the microcycle had a significant effect on the workload both in volume and intensity (F = 4.84–14.19; p < 0.01; wp 2 = 0.03–0.09), except for relative ACCHIGH, DECHIGH, and HMLD. Although MD-4 and MD-3 were the most suitable days for loading the players, the results showed that MD elicited a unique stimulus in terms of volume and intensity. Consequently, coaches need to include specific training drills to adapt the players for the competitive demands. Finally, special focus should be placed on MD from short and regular microcycles (5-day, 6-day, or 7-day microcycles) since declines in physical performance were observed in comparison with long microcycles (8-day or 9-day microcycles).